The equation x 4 − 2 x 3 − 5 x 2 + 1 0 x − 3 = 0 has four different real solutions a , b , c , d find the value of a c b d if a > b > c > d .
You may want to use a calculator.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x 4 − 2 x 3 − 5 x 2 + 1 0 x − 3 = 0
( x 2 − 3 x + 1 ) ( x 2 + x − 3 ) = 0
x 2 − 3 x + 1 = 0
x 2 + x − 3 = 0
The solutions for both equations are 2 3 ± 5 and 2 − 1 ± 1 3 Then the value of a c b d = . 7 8 5 .
Sorry if my solution is not elegant i will post another one in a few days.
how do you factorise this equation
Problem Loading...
Note Loading...
Set Loading...
Set x 4 − 2 x 3 − 5 x 2 + 1 0 x − 3 = ( x 2 + α x + β ) ( x 2 + γ x + δ ) = x 4 + ( α + γ ) x 3 + ( β + δ + α γ ) x 2 + ( α δ + β γ ) x + β δ . Equating coefficients produces the following system of equations:
α + γ = − 2 (1)
β + δ + α γ = − 5 (2)
α δ + β γ = 1 0 (3)
β δ = − 3 (4)
Assume α , β , γ , δ are all integers. Looking at equation (4), there are only two possibilities for the integer pair, β and δ , that are not ultimately equivalent: β = 1 , δ = − 3 and β = − 1 , δ = 3 .
First, I'll try β = − 1 , δ = 3 to see if it satisfies the other equations. Substituting these values into equation (3) gives 3 α − γ = 1 0 . Combining this equation with equation (1) gives α = 2 , γ = − 4 . Next, substitute these found values into equation (2) to see if it is satisfied. The result is − 1 + 3 + ( 2 ) ( − 4 ) = − 6 = − 5 . So, the system is not satisfied with β = − 1 , δ = 3 .
Finally, I try β = 1 , δ = − 3 . Substituting these values into equation (3) gives − 3 α + γ = 1 0 . Combining this equation with equation (1) gives α = − 3 , γ = 1 . Then we test these values in equation (2) and see that it is satisfied. Thus, the system is solved by α = − 3 , β = 1 , γ = 1 , δ = − 3 . These values lead to the following factorization for x 4 − 2 x 3 − 5 x 2 + 1 0 x − 3 :
( x 2 − 3 x + 1 ) ( x 2 + x − 3 )
From there, I just used the quadratic formula and a calculator to find the ordering of the roots and then, of course, used a calculator again to calculate a c b d ≈ 0 . 7 8 5 .